ChemInform Abstract: Cobalt‐Catalyzed Synthesis of Quinolines from the Redox‐Neutral Annulation of Anilides and Alkynes. Issue 40 (September 2016) - Yan, Qiangqiang; Chen, Zhengkai; Liu, Zhanxiang; Zhang, Yuhong
Abstract: This new method shows a remarkable regioselectivity in the case of meta‐substituted anilides (IVa, b) and unsymmetric acetylenes (VIII).